MANAGEMENT OF SECONDARY ANGLE-CLOSURE GLAUCOMA IN ANTERIOR SEGMENT DYSGENESIS AND ANTERIOR MICROPHTHALMOS PATIENT - syifa rahmani; Maula Rifada (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: The majority of cases of anterior segment dysgenesis (ASD) and anterior microphthalmia are known to be complicated by angle-closure glaucoma, which is also the primary cause of visual loss. Medical therapy of this secondary glaucoma is frequently ineffective, necessitating surgery. However, managing the surgery in an eye with a crowded anterior chamber is difficult. This study aimed to report the management of secondary angle-closure glaucoma in anterior segment dysgenesis and anterior micropthalmos patient. Case Report: : A 39-year-old woman presented to Glaucoma unit with chief complaint of pain on the right eye. She also noted blurred vision, redness, and headache approximately seven months before presentation. The patient had a history of glaucoma since 5 years old, but hadn’t regularly visit for a long time. The visual acuity was 1/60 and intraocular pressure (IOP) was 45. Anterior segment evaluation revealed scleral thinning with injection, microcornea, sclerocornea, hazy peripheral cornea, iridocorneal adhesion, shallow anterior chamber, iris transillumination defect and lens opacity. A-scan biometry showed normal axial length. She was diagnosed with secondary angle-closure glaucoma with anterior segment dysgenesis, anterior microphthalmia and presenile cataract of the right eye. The patient underwent combined phacotrabeculectomy, pars plana vitrectomy and intraocular lens implantation. Discussion: Surgical procedure is indicated if pharmacological therapy cannot control IOP and glaucoma progressivity, including trabeculectomy combined with cataract extraction. However, cataract extraction is more difficult in shallow anterior eye chamber because the working field is narrower and the distance between the cornea and lens is closer. Some strategies to prevent this include pars plana vitrectomy (VPP). Conclusion: Anterior segment dysgenesis, though rare, cause vision loss by glaucoma as complication. Treatment of secondary glaucoma aim to lowering IOP to halt its progression. Combined phacotrabeculectomy, pars plana vitrectomy and intraocular lens implantation was a safe procedure in this crowded anterior chamber eye.